2011
DOI: 10.1177/0194599811415823a404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peak Nasal Inspiratory Flow as an Objective Method of Measuring Nasal Airflow

Abstract: POSTERSclinical features of ACPs in Japan is very limited. Here, we performed a prospective study to evaluate the prevalence and clinical features of ACPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 0 publications
4
31
0
6
Order By: Relevance
“…It is well documented that nasal congestion is correlated with restricted lower nasal airflow function in adults with seasonal rhinitis . Key studies have demonstrated that PIFR measurements reflect the severity of nasal signs of rhinitis in a general population sample of young adults . The strong association between PFIR and rhinitis signs in this study provides objective and complementary evidence of the decrease in response and symptom scores of the patient, during nasal challenge testing.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is well documented that nasal congestion is correlated with restricted lower nasal airflow function in adults with seasonal rhinitis . Key studies have demonstrated that PIFR measurements reflect the severity of nasal signs of rhinitis in a general population sample of young adults . The strong association between PFIR and rhinitis signs in this study provides objective and complementary evidence of the decrease in response and symptom scores of the patient, during nasal challenge testing.…”
Section: Discussionsupporting
confidence: 57%
“…), highlighting the clinical effectiveness of treatment of patients in this cohort. It is well documented that nasal congestion is correlated with restricted lower nasal airflow function in adults with seasonal rhinitis . Key studies have demonstrated that PIFR measurements reflect the severity of nasal signs of rhinitis in a general population sample of young adults .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, mean PNIF recordings were within the normal range in both groups, demonstrating that nasal airflow was unimpeded. 16,25 This suggests that a process other than physical resistance to airflow in the nasal cavity was responsible for the subjective impression of nasal obstruction in our CRS patients. TS chemoreception was known to relay information about freshness and coolness within the nasal cavity, but Zhao and colleagues were the first to demonstrate that mucosal cooling was the mechanism driving the sensation of patency.…”
Section: Discussionmentioning
confidence: 81%
“…CRS patients rated their sensation of nasal obstruction to be significantly worse than controls, and both groups demonstrated similar mean PNIF measurements. In fact, mean PNIF recordings were within the normal range in both groups, demonstrating that nasal airflow was unimpeded . This suggests that a process other than physical resistance to airflow in the nasal cavity was responsible for the subjective impression of nasal obstruction in our CRS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although inspiratory manoeuvres may cause alar collapse and thus valve insufficiency, and in few cases, when the nose is totally blocked, it is not possible to obtain a measurement , PNIF has some undoubtable hygienic advantages over PNEF . Moreover, it seems that PNIF correlates better with nasal resistances than PNEF .…”
Section: Objective Measurements Of Nasal Airflow and Patencymentioning
confidence: 94%